G417(P) Does sharing care processes completeness information with patients/parents increase their willingness to engage with self-management?. (25th October 2020) - Javed, MS; Lane, T; Tong, C; Wood, B; Killops, A; McCausland, D; Zoualghina, R; Coates, D
Abstract : Aim: Test the hypothesis that informing patients looked after by paediatric diabetes team about results of their care processes over the year will improve their commitment to self-management with view to improving diabetes care. Background: Paediatric diabetes team sent a three page annual report to all of their patients. First page was used to reinforce the importance of all annual care processes. Second page was personalised for each patient to list the completion status/results of annual care processes and included a table and colour coded graph of their HbA1c values. The third page listed few personalised recommendations to help patients set their treatment goals for next year. All patients/parents were invited to an online survey to give their views after receiving this report. Results: Total 49 responses were received including 17 responses from young persons. Knowledge of essential care processes was good with only 2 responses denying knowledge of thyroid function tests and 1 denying knowledge of BMI assessment. Knowing results of blood pressure, urine albumin creatinine ratio and cholesterol were felt 'not useful' by only 4.1% of respondents and only 2% respondents felt the letter did not help them setting goals for next year. 89.8% of respondents found colour coded HbA1c graph 'extremely useful' or ' 'very useful' and 10.2% found it somewhat useful. 71.4% respondents said they will put more effort in their diabetes care next year, 14.2% said 'about the same effort' and 14.2% were 'not so sure'. 95.9% respondents would like to have similar letter next year. One respondent said, 'I feel like I should take it more seriously because I need to be in the green zone.' Conclusion: Majority of respondents found information on care process completion status useful and wanted to have similar report next year. Majority of respondents said they will put more effort in their diabetes care favouring hypothesis that informing patients about their care processes and results increases willingness to learn self-management. However, considering anonymous nature of the survey, it will not be possible to see if individual patients made real improvement in their diabetes care after receiving this report.